Teachers’ Strategies in Teaching English Vocabulary in Secondary Schools - Lulu Syifa Fadhila (JELT : Journal of English Education, Teaching and Literature, 2026)
This study aims to explore teachers’ strategies in teaching English vocabulary in secondary schools. The research employed a qualitative descriptive design to obtain an in-depth understanding of how teachers implement vocabulary instruction in classroom settings. The participants of this study were English teachers selected through purposive sampling based on their teaching experience and involvement in vocabulary instruction. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing. The findings revealed that teachers used a variety of strategies in teaching vocabulary, including translation, explanation, repetition, memorization, contextual teaching, interactive activities, game-based learning, and the use of media. Among these strategies, contextual and interactive approaches were found to be more effective in enhancing students’ understanding and use of vocabulary, while traditional methods such as memorization were mainly effective for short-term retention. The study also found that teachers often combined multiple strategies to address different learning needs and classroom conditions. However, several challenges were identified, such as limited time, large class sizes, varying student abilities, and lack of technological resources. In conclusion, the effectiveness of vocabulary teaching strategies depends on how they are implemented and adapted to students’ needs. Teachers are encouraged to adopt a balanced and student-centered approach by integrating various strategies to promote meaningful learning and improve students’ vocabulary mastery.